POWER CURVE PREDICTION OF SMALL SCALE WIND TURBINE REFERRING TO THE GENERATOR CHARACTERISTIC - Irasari, Pudji; Candra, Dodiek Ika (LIPI Press, 2013)
This paper discusses power curve prediction of small scale wind turbine for a battery charger. The proposed prediction method does not require the data of wind speed but refers to the generator characteristic instead. The method is based on wind turbine power equation initiated with determining the value of Cp, then establishes the powerwind speed and shaft speedwind speed correlations. For simplicity, this method ignores aerodynamic factor of the system. The simulation result in the form of wind turbine power curve (power versus wind speed graph) is then compared with the characteristics of commercial wind turbine and demonstrates rational values of cut-in and cut-out wind speed.